Diagnosing bias in data-driven algorithms for healthcare - Wiens, Jenna; Price, W. Nicholson; Sjoding, Michael W. (Nature medicine, 2020)
A recent analysis highlighting the potential for algorithms to perpetuate existing racial biases in healthcare underscores the importance of thinking carefully about the labels used during algorithm development.